OCP, a Strategic Pillar of the Moroccan Economy: An Analysis of Its Impact and the Leadership of Mr. Mostafa Terrab - El Kiasse, Rafik; Frejus, Freddy (European Journal of Applied Sciences, 2025)
The Office Chérifien des Phosphates (OCP), a flagship of the Moroccan economy, plays a crucial role in positioning the Kingdom on the global economic stage. This article aims to analyze the strategic importance of OCP for Morocco’s economy through its contribution to GDP, employment, exports, and sustainable development projects. Furthermore, the visionary management of its CEO, Mr. Mostafa Terrab, is a key factor in the modernization and internationalization of the group. This study is based on a documentary analysis of institutional, academic, and media sources, combined with an exploratory qualitative approach. The findings reveal that OCP goes beyond being a phosphate producer: it acts as a catalyst for industrial transformation, innovation, and South-South partnerships. Under the leadership of Mr. Terrab, driven by managerial excellence and African engagement, the group has achieved remarkable performance on the global stage while reinforcing its role as a driver of national socio-economic development.